Hubungan Kecepatan Lari Daya Ledak Tungkai dan Kelentukan Togok ke Depan dengan Kemampuan Lompat Jauh - Bakar, Abu; Mardiah, Ainun; Kurniadi, Agus (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study aims to determine whether there is a relationship between running speed and long jump ability, a relationship between leg explosive power and long jump ability, a relationship between forward leg flexibility and long jump ability, and a relationship between running speed, leg explosive power, and togok flexibility in the future together with the long jump ability. The research population are students at the SD Inpres Bertingkat Mamajang II Makassar and the sample used was 40 people. The sampling technique is purposive sampling. The data analysis technique used is product moment correlation coefficient (r) and multiple correlation (R) at a significance level of 5%. As the results show that: there is a significant relationship between running speed and long jump ability as proven by the calculated r value (r0)=-0.635, there is a significant relationship between leg explosive power and long jump ability is proven by the calculated r value (r0) = 0.821, there is a significant relationship between the flexibility of the forward stroke and the long jump ability, proven by the calculated r value (r0) = 0.483, there is the jointly significant relationship between running speed, leg explosive power and forward movement flexibility and long jump ability was proven by the calculated R value (R0) = 0.833.